Effect of Plant Population and Integrated Nutrient Management on Yield of Yard Long Bean (Vigna unguiculata) - Kakon, S S; Paul, S; Begum, A A; Chowdhury, J A; Zannat, S T (Bangladesh Agronomy Journal, 2025)
The experiment was conducted at Agronomy Research Field of BARI, Gazipur during Kharif-1 seasons of 2020-21 and 2021-22 to evaluate the effect of manures and fertilizers and optimum plant population for higher yield of yard long bean. Two planting geometry, viz., P1= 45 cm × 30 cm (8 plants m−2) P2= 40 cm × 20 cm (12.5 plants m−2) and three nutrient levels viz., F1=Recommended fertilizer dose (RFD) (21-27-33-9-1.2-1.2 kg ha−1 NPKSZnB), F2= IPNS (16-25-30-9-1.2-1.2 kg ha−1 NPKSZnB) + Poultry manure (PM) (3 t ha−1) and F3 = IPNS (16-25-30-9-1.2-1.2 kg ha−1 NPKSZn) + Vermicompost (VC) (3 t ha−1) were used. The integrated treatment combinations involve both organic and inorganic source of nutrients which significantly influenced the growth and yield attributes. The better results in terms of vegetable fresh yield were obtained in the following order: PM > VC> NPK. Application of VC is not beneficial due to 15 times higher price than PM. The result indicated that plant spacing of 40 cm ´ 20 cm with PM added NPK fertilizer combination (F2) gave the maximum pod yield (4.90 t ha−1 in 2020-21 and 4.83 t ha−1 in 2021-22) which was statistically similar to same spacing with VC added NPK fertilizer combination (F3) but the highest benefit cost ratio (2.15) was recorded in plant spacing of 40 cm ´ 20 cm with PM added NPK fertilizer combination (F2). From the result it might be could be concluded that plant spacing of 40 cm × 20 cm (1,25,000 plants ha−1) with organic and inorganic source of nutrients {IPNS (16-25-30-9-1.2-1.2 kg ha−1 NPKSZn) with PM (3 t ha−1)} was found to achieve the maximum productivity of yard long bean cultivation at Gazipur. Bangladesh Agron. J. 2024, 27(1): 23-28